The formation of Cuban track and field champions - Muniz Sanabria, A. (New Studies in Athletics, 2011)
Although it has a relatively small population base, Cuba has consistently been an athletics power for more than half a century and its athletes have won Olympic and World Championship medals in 26 events. The nation`s success has been achieved with the support of a well-planned and scientifically-based athlete development process, which has made international researchers, professionals and specialists wonder about the Cuban secret for producing champions.